(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2024)
Materials and methods: herbarium collections, literature data, field observations. Nomenclature: POWO 2024, World Plants 2024, Euro+Med Plant Base 2024 Results: In the flora of Ukraine, the order Geraniales includes one family, Geraniaceae. The family Geraniaceae is represented by three genera, namely, Erodium, Geranium, and Pelargonium comprising 32 species of autochthonous and cultivated floras. Erodium cyconioides is a synonym of E. ciconium. Features by which the subspecies Geranium sibiricum subsp. popovii are unstable and fall within the range of variability of typical G. sibiricum. The species name G. alpestre is illegitimate and should be replaced by G. sylvaticum, which should also include plants from the vicini-ty of Kremenets (Ternopil region), which were defined as G. uralense. The family Linaceae in the flora of Ukraine is represented by 24 species (including subspecies), which are part of two genera (Linum and Radiola). The species name Linum angustifolium is a synonym of L. bienne. The species L. catharticum in Ukraine is represented by a typical variety. Among the species close to L. corymbulosum, which is widespread in the Crimea, L. strictum, L. trigynum and L. gallicum are erroneously cited for the Crimea (the latter is a synonym of L. trigynum, which is widespread in Transcarpathia). Synonyms of L. hirsutum are L. cretaceum and L. lanuginosum. The species Linum nervosum in Ukraine is represented by two subspecies: L. nervosum subsp. jailicola (in Mountainous Crimea) and typical L. nervosum subsp. nervosum, which synonym is L. aucheri, reported from the Crimea. A synonym of L. squamulosum is L. euxinum. The species L. usitatissimum, which is cultivated in Ukraine, is represented by the typical variety, which was previously also referred to as: L. crepitans and L. humile.